PENERAPAN ILMU MATEMATIKA PADA ILMU EKONOMI : SISTEM BILANGAN - Ramadhani, Agil Tri; Ayu Hermawan, Amanda Zafira; Kartika, Lisda; Bachrul Ulum, Mochammad; Vicky Hermawan, Mohammad; Dellavana, Navilsa; Syahputri, Nesa Nanda (JIEM : Journal Of International Entrepreneurship And Management, 2024)
This research aims to analyze number system material which focuses on the whole number system and the natural number system. This article discusses the learning media used in delivering material on the whole number system and the natural number system so that it can facilitate the understanding of the material presented by normal to deaf audiences. This research uses a literature review method by taking 20 articles for analysis. 20 articles are detailed, 10 articles discuss whole numbers and the other 10 articles discuss natural numbers. Of the 20 articles analyzed, this research shows that audience understanding increases drastically when using learning media in the process of delivering material. In this context, it is not only related to one material, the two materials discussed are the whole number system and the alsi number system material, but both materials have the same result, namely that the learning media has a big influence on the audience's speed of understanding